Traditional Medicine in The Littoral and Neritic Zones - Patriscia Frans; Fadhia Rifa Amalia; Adinda Qomairoh Vinancya Bokingo (Asia Pacific Journal of Interdisciplinary Studies, 2025)
Brown algae (*Phaeophyceae*), particularly *Sargassum sp.*, play a significant role in traditional medicine due to their rich bioactive compounds. This study explores the potential and utilization of brown algae as pharmaceutical ingredients, focusing on their presence in the littoral and neritic zones. *Sargassum sp.* is known for its antioxidant, anti-inflammatory, and antimicrobial properties, contributing to the prevention and treatment of various health conditions, including skin diseases, digestive disorders, and respiratory ailments. The polysaccharides and phenolic compounds in brown algae, such as phlorotannins, provide significant health benefits and are used in modern pharmaceutical applications, including stroke prevention and immune system enhancement. This research highlights the importance of sustainable utilization and quality control in the use of algae-based medicines to ensure safety and efficacy. With further scientific advancements, brown algae have the potential to revolutionize the pharmaceutical industry and improve public health.